Are the corporate voluntary disclosures and transparency in the transitional economy better than the pre-transitional economy? Evidence from developing country - Abdullah, Shamsul Nahar; Masum, Mofijul Hoq; Alam, Mohammad Faridul (International Journal of Management and Sustainability, 2024)
The study’s goal is to explore the role of corporate voluntary disclosure and transparency as a strategic tool rather than corporate reporting techniques. This empirical study employs a comparative approach to identify the variations in corporate voluntary disclosure in the pre-transitional and transitional stages of a developing country. A paired sample of 307 annual reports of the Dhaka Stock Exchange (DSE) listed companies is considered to explore their reporting practices between the pre-transitional and transitional stages. Lately, a paired t-test has been conducted to examine whether corporate voluntary disclosure significantly differs between the pre-transitional economy and transitional economy. It is found that the corporate people disclose more information in the transitional phase of the emerging economy rather than the pre-transitional phase. The findings of the study will assist emerging countries in designing their corporate strategies to achieve the Sustainable Development Goal (SDG). The study suggests that using voluntary disclosure as a strategic tool can help retain and attract both existing and prospective investors. This study also helps the regulatory body shape its macro-level corporate strategy to successfully graduate from the LDC to the developing economy. Moreover, this study will assist the transitional economy to transform from an aid-based economy to a trade-based economy.